The Effect of Gamification of Four-Grade Students’ Writing Competency - Kadek Gita Suryani; I Gede Yoga Permana (International Journal of Digital Learning on Languages and Arts (IJODLLA), 2024)
This research aims to determine the effect of gamification on fourth grade students' writing competence. This study was an experimental study conducted at SD N 4 Banyuasri, Buleleng, Bali. Using pretest posttest design, this study involved four grade students as the sample of the study. Data collection in this research used several instruments, namely tests (pre-test and post-test), lesson plans, and rubric for analyzing writing. The results of the study found that the post-test score (M= 82.86, Std= 7.507) was higher than the pre-test (M= 42.32, Std= 14.368). The t test results also confirmed that there was a significant difference in the mean score between the pre-test and post-test (Sig≤0.05). During the learning process, students look active and motivated while participating in the learning process in class. This study also present an important discussions towards using gamification in creating motivating and engaging learing environment.